ASSESSMENT OF THE CHANGE IN RIVER DISCHARGE-CARRYING CAPACITY USING REMOTE SENSING GEOGRAPHIC INFORMATION SYSTEM: A CASE STUDY OF OFU RIVER, NIGERIA (Nigerian Journal of Technology, 2018)
This study assessed the changes in the flow carrying capacity of Ofu River in Nigeria between 2000 and 2011 using the DEMs of the respective years. The results showed that Ofu River had lost 12.88 m amounting to about 42.58 % of its flow depth at Oforachi between 2000 and 2011 at a rate of 1.171 m per year and an estimated 18.74 m amounting to about 61.95 % in 2016. The Total sediment load was 66,825,730 kg/year comprising of 56,747,260 kg/year and 10,077,470 kg/year of measured and unmeasured sediment loads respectively. The results obtained suggested that the loss in flow depth is a result of siltation of the river bed due to the high sediment load probably as a result of soil cultivation within the floodplains. The study demonstrated that remote sensing and GIS can be used to assess the changes in the discharge-carrying capacity of a river. http://dx.doi.org/10.4314/njt.v37i3.36